ANALYTICAL STUDY OF SOME CLIMATIC AND HYDROLOGIC PARAMETERS DEPENDING ON RAINFALL OF FOREST STANDS IN NENEVAH - Ibrahim I. A (Mesopotamia Journal of Agriculture)
Analytical study of local climate and hydrology of forest stands were done at Nenevah plantations. The study involved analysis of some climatic parameters of 2002 and gross precipitation data since September (2003) till April (2006). The results indicated that the mean of relative humidity during winter months ranged between 66% - 84% and effective temperature was more than 24 ْ C during June and July which caused sultriness feeling, also increasing of vapor pressure was noticed in these months as compared to winter months, maximum and minimum amounts of saturation deficit in July and February were 35.4, 1.04 mb respectively , means of dew point and wet bulb of these months were 19.5 ْ C and 24 ْ C respectively. Amount of precipitation varied from 285 mm to 404mm during study period. maximum throughfall of Pinus brutia, Eucalyptus camaldulensis , and Platanus occidentalis were respectively 269,342,363mm during 2006 water year, but amounts of runoff estimated by depending on runoff coefficient method of 2004,2005,2006 water years were 46, 42, 60 mm respectively.